Personal Protective Equipment Compliance in Midwifery Services in Eastern Indonesia - Ignasensia Dua Mirong; Dewa Ayu Putu Mariana Kencanawati; Ummu Zakiyah; Rizky Setiadi (Indonesian Journal of Global Health Research, 2023)
At the begining of pademic, Indonesiam goverment suggested that midwifery services be carried by using appropriate personal protective equipment according to the guidelines to avoid cross-infection between health worker to mother and child. The purposes of this strudy is to determine the midwife's compliance in following the use of PPE when administering mother and child health services during COVID 19 pandemic. This survey was conducted at the begining of pandemi COVID-19, 403 registered midwives participated by filled an online survey with Google form application for data collection. Variable of this research are midwife compliance of using PPE in midwifery services. The data were analyzed using the statistical test used was Pearson's chi-square. Results showed that 89.8% of midwives were not following the health protocol, as 49.8% offered inadequate PPE in the workplace and the price of PPE was very high during the pandemic. Conclusions: Midwives were unable to comply with the use of personal health and safety equipment (PPE) in services. Age and duration of work had factor had a significant impact on whether or not midwives were able to use PPE appropriately.